DERIVATIVES OF THE RATIO SPECTRA FOR DETERMINATION OF ACETYLSALICYLIC ACID, ACETAMINOPHEN, AND CAFFEINE IN FIXED-DOSE COMBINATION FORMULATIONS: APPLICATION TO DISSOLUTION STUDIES - MEDINA-LÓPEZ, JOSE RAUL; PACHECO PINEDA, JOSUE GIOVANI; ROJAS GARFIAS, PEDRO ALBERTO; CASTRO CHÁVEZ, NICASIO (International Journal of Applied Pharmaceutics, 2020)
Objective: To develop a ratio-derivative spectrophotometric method for the simultaneous quantification of acetilsalycilic acid (ASA), acetaminophen (ACE), and caffeine (CAF) in fixed-dose combination formulations. The proposed method was applied to the reference drug product Excedrin® in dissolution studies. Methods: The method is based on the use of the first-and second-derivatives of the ratio spectra and measurements at zero-crossing wavelengths. The dissolution profiles of ASA, ACE, and CAF were obtained following pharmacopeial conditions, USP Apparatus 2 at 100 rpm and 900 ml of water. Dissolution samples were treated with the proposed UV-derivative method and the results were compared with those obtained with a validated HPLC procedure. The dissolution efficiency was used to compare dissolution profiles (HPLC vs. UV-derivative method). Results: The method was linear in the range of 5-25 µg/ml of ASA, 2.5-20 µg/ml of ACE, and 1-8 µg/ml of CAF (R2>0.999, *P<0.05). The precision and accuracy of synthetic mixtures were within acceptable criteria (2.11-3.43% and 96.78-104.15%, respectively). Nitrocellulose filters were the best option to filter samples and stability of all drugs was adequate when standard solutions were stored at 4 °C during 24 h. No significant differences were found between dissolution profiles (*P>0.05). Conclusion: The proposed UV-derivative method allows the simultaneous determination of ASA, ACE, and CAF in commercial formulations. The method is simple, accurate, and precise and can be used in dissolution studies. Spectrophotometric methods are of low cost and harmless to the environment and, therefore, a better alternative than chromatographic methods.